Factors contributing to visual intrapartum cardiotocograph interpretation variation among healthcare professionals: An integrative review - Sanele Lukhele; Fhumulani Mavis Mulaudzi; Rodwell Gundo (PLoS ONE, 2025)
The reliability of cardiotocographs as diagnostic tools for fetal well-being is hampered by interpretational variations among healthcare professionals, contributing to high rates of cesarean sections and instrumental deliveries. While adjunct technologies may be used to confirm cases of fetal distress, those in resource constrained areas continue to rely on visual cardiotocograph interpretation to come up with the diagnosis of fetal hypoxia. This study investigated the factors contributing to variations in the visual interpretation of intrapartum cardiotocograph among healthcare professionals in the absence of adjunctive technologies. In this integrative literature review, we conducted a literature search of the following electronic databases: EBScohost, PubMed, Web of Science, and Scopus. The following search terms and Boolean operators were used: (Intrapartum OR Labor OR Labour OR Childbirth OR Birth OR Delivery) AND (Cardiotocography OR CTG OR "Electronic Fetal Monitoring" OR EFM) AND (Interpretation OR Analysis) AND (Variations OR Differences) AND (“Healthcare Workers” OR Nurses OR “Medical Workers” OR “Healthcare Professionals” OR Midwives OR Obstetricians). After removal of duplicates, a total of 1481 articles and titles were screened, 60 full-text articles were examined to verify whether they addressed the scope of the literature review. Nine articles addressed the factors contributing to variations in the visual interpretation of intrapartum cardiotocographs among healthcare professionals. The quality of the studies was appraised using the Quality Appraisal Tool for Studies of Diagnostic Reliability. Thematic analysis identified the following themes: 1) Interpretational variations in cardiotocograph characteristics among health professionals, and 2) factors leading to increased interpretational variation among healthcare professionals. Our results highlight the need for increased cardiotocograph training to improve consistency among health professionals, especially for suspicious and pathological traces, which often lead to cesarean section.